Tunnel Contacts for Spin Injection into Silicon: The Si-Co Interface with and without a MgO Tunnel Barrier—A Study by High-Resolution Rutherford Backscattering - S. P. Dash; D. Goll; P. Kopold; H. D. Carstanjen (Advances in Materials Science and Engineering)
In order to obtain high spin injection efficiency, a ferromagnet-semiconducor Schottky contact must be of high crystalline quality. This is particularly important in the case of ferromagnet-silicon interfaces, since these elements tend to mix and form silicides. In this study Co-Si (100) interfaces were prepared in three different ways: by evaporation at room temperature, low temperature (−60∘C), and with Sb as surfactant, and their interface structures were analyzed by high-resolution RBS (HRBS). In all cases more or less strong in-diffusion of Co with subsequent silicide formation was observed. In order to prevent the mixing of Co and Si, ultra thin MgO tunnel barriers were introduced in-between them. In situ HRBS characterization confirms that the MgO films were very uniform and prevented the mixing of the Si substrate with deposited Co and Fe films effectively, even at 450∘C.